Preserving cultural entity amidst growing ecotourism in Mabul Island, Malaysia - Radieah Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Ecotourism should promote environmental protection and improve the welfare of local communities. However, the changes brought by ecotourism are not always positive, raising concerns about the destruction of traditional lifestyles, environmental degradation and socio-economic inequalities. This study examines how the Suluk and Bajau communities on Mabul Island adapt to these changes and identifies strategies to strengthen their resilience while ensuring the sustainability of ecotourism. This qualitative study, using a scoping review, found that changes in land use and the economy on Mabul Island are linked to environmental degradation and human intervention. Communities involved in traditional livelihoods, such as fishing, demonstrate greater resilience as they are less dependent on the tourism economy. However, those relying on ecotourism activities, such as hospitality, tour guiding and transportation, face challenges when tourism declines. While tourism has brought economic benefits, it has also highlighted vulnerabilities, particularly in terms of dependence on external socio-economic factors and environmental damage. To enhance resilience, communities should promote sustainable ecotourism, preserve traditional knowledge and implement strategies to protect natural resources. Additionally, Mabul Island can combine various forms of sustainable tourism by adopting innovative strategies such as community-led tourism initiatives, stricter environmental regulations and promoting cultural tourism.